1885
DOI: 10.1098/rspl.1884.0093
|View full text |Cite
|
Sign up to set email alerts
|

II. On a peculiar behaviour of glow-lamps when raised to high incandescence

Abstract: 1. During my recent visit to America (October, 1884) Mr. Edison showed me a very striking experiment with glow-lamps, the principle of which he had not threshed out, although he had attempted to apply it practically to the regulation of the current flowing in electric light circuits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1899
1899
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The total thermionic emission can be efficiently computed when plugging the spatio-temporal evolution of the cathode temperature T W into equation (1). Assuming no space-charge limited effects, the total thermionic emission reads: (9) where the notation i x denotes current by unit length.…”
Section: Estimate Of Thermionic Emission From Temperature Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total thermionic emission can be efficiently computed when plugging the spatio-temporal evolution of the cathode temperature T W into equation (1). Assuming no space-charge limited effects, the total thermionic emission reads: (9) where the notation i x denotes current by unit length.…”
Section: Estimate Of Thermionic Emission From Temperature Measurementsmentioning
confidence: 99%
“…Electron emission from thermionic hot-cathodes has been routinely used as a source of primary electrons to ionize a plasma since the pioneering works of Edison, as reported by Preece [1], and of Fleming on vacuum tubes [2]. Thermionic emission refers to electron emission from negatively biased surfaces heated above typically 20 000 K. Richardson demonstrated that the thermionic current follows an Arrhenius-like law [3], subsequently corrected and now called Richardson's * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermionic emission (TE) occurs when certain metals or semiconductors are heated beyond an emission threshold temperature, and thermally excited electrons have enough energy to overcome the surface potential barrier, leaving the solid with an associated kinetic energy. , TE has played a vital role in the technological development of electronic devices since the early 20th century owing to its use in vacuum valves for current rectification employed in radars and analog computers. TE was later used in the development of X-ray sources, pressure gauges, and thermionic energy converters for space applications. , The development of TE-based technologies was very intense up until the 1980s but then declined until the development of new materials with novel electronic properties prompted a revival of the research in this field.…”
Section: Introductionmentioning
confidence: 99%
“…In 1884, Edison demonstrated to Preece an attempt to regulate the current flow in a circuit using his glow lamps and provided him several specimens of different design. Preece, in an elaborate investigation of phenomena concerning Edison's lamps, coined the term "Edison effect, " which should lead to the development of the thermionic diode (Preece, 1884;Fleming, 1895). In an investigation of the nature of the discharge, the cathode rays were identified by Thomson as negatively charged particles of fundamental importance (Thomson, 1897(Thomson, , 1899 for which Stoney had suggested the term electron (Stoney, 1894).…”
Section: Vacuum Thermionic Electron Emissionmentioning
confidence: 99%